Methane Exhalation Can Monitor the Microcirculatory Changes of the Intestinal Mucosa in a Large Animal Model of Hemorrhage and Fluid Resuscitation - Bársony, Anett; Vida, Noémi; Gajda, Ámos; Rutai, Attila; Mohácsi, Árpád; Szabó, Anna; Boros, Mihály; Varga, Gabriella; Érces, Dániel (Frontiers in Medicine, 2020)
Background: Internal hemorrhage is a medical emergency, which requires immediate causal therapy, but the recognition may be difficult. The reactive changes of the mesenteric circulation may be part of the earliest hemodynamic responses to bleeding. Methane is present in the luminal atmosphere, thus we hypothesized that it can track the intestinal circulatory changes, induced by hemorrhage, non-invasively. Our goal was to validate and compare the sensitivity of this method with an established technique using sublingual microcirculatory monitoring in a large animal model of controlled, graded hemorrhage and the early phase of following fluid resuscitation. Materials and Methods: The experiments were performed on anesthetized, ventilated Vietnamese minipigs (approval number: V/148/2013; n=6). The animals were gradually bled seven times consecutively of 5% of their estimated blood volume each, followed by gradual fluid resuscitation with colloid (hydroxyethyl starch; 5% of estimated blood volume/dose) until 80 mmHg mean arterial pressure was achieved. After each step, macrohemodynamic parameters were recorded and exhaled methane level was monitored continuously with a custom-built photoacoustic laser-spectroscopy unit. The microcirculation of the sublingual area, ileal serosa and mucosa was examined by intravital videomicroscopy (Cytocam-IDF, Braedius). Results: Mesenteric perfusion was significantly reduced by a 5% blood loss, while microperfusion in the oral cavity deteriorated after a 25% loss. A statistically significant correlation was found between exhaled methane levels, superior mesenteric artery flow (r=0.93) or microcirculatory changes in the ileal serosa (ρ=0.78) and mucosa (r=0.77). After resuscitation, the ileal mucosal microcirculation increased rapidly (De Backer score (DBS): 2.36±0.42 vs 8.6±2.1 mm-1), while serosal perfusion changed gradually and with a lower amplitude (DBS: 2.51±0.48 vs 5.73±0.75). Sublingual perfusion correlated with mucosal (r=0.74) and serosal (r=0.66) mesenteric microperfusion during the hemorrhage phase but not during the resuscitation phase. Conclusion: Detection of exhaled methane levels is of diagnostic significance during experimental hemorrhage as it indicates blood loss earlier than sublingual microcirculatory changes and in the early phase of fluid resuscitation the exhaled methane values change in association with the mesenteric perfusion and the microcirculation of the ileum.